Biometric and reproductive aspects of Anadara tuberculosa (Sowerby, 1833) (Bivalvia: Arcidae) in two extraction sites, Esmeraldas and El Oro, Ecuador, during the last quarter of 2016 - Moreno, Juan; Alemán, Carlos; Bonilla, Roger E. (Revista Ciencias Marinas y Costeras, 2019)
As a result of a series of projects, a comparative analysis was conducted from October to December 2016 between four natural cockle (Anadara tuberculosa) banks located in the provinces of Esmeraldas (bordering with Colombia) and El Oro (bordering with Peru) in order to determine the reproductive condition of the species and its size distribution. A total of 2474 samples were collected and measured with a digital caliper. To determine their sex and sexual maturity, gonads were macroscopically observed by making a transversal cut to the visceral mass. The Mann- Whitney nonparametric test was used to compare extraction sites by size distribution. Average sizes according to extraction sites were: Coronera (47.82 mm) and Feliciano (44.02 mm) in Esmeraldas and Grabadora (45.44 mm) and Bravito (43.42 mm) in El Oro. The reproductive condition was predominantly the spawning stage during the period from October to December. The calculation of the Chi-square indicates that the temperature observed in the months analyzed did not influence the stage of maturity in Esmeraldas (P=0.18) or in El Oro (P=0.83). Comparing extraction sites exhibited significant differences (P